12.1k views
1 vote
Solve by completing the square :

4x^2-12x+7=0

User Bcody
by
5.3k points

1 Answer

1 vote

Answer:


x=(3)/(2)\pm(√(2))/(2)}

Explanation:

we have


4x^2-12x+7=0

step 1

Group terms that contain the same variable, and move the constant to the opposite side of the equation


4x^2-12x=-7

step 2

factor the leading coefficient


4(x^2-3x)=-7

step 3

Complete the square. Remember to balance the equation by adding the same constants to each side


4(x^2-3x+1.5^2)=-7+1.5^2(4)


4(x^2-3x+2.25)=2

simplify


(x^2-3x+2.25)=0.5

step 4

Rewrite as perfect squares


(x-1.5)^2=0.5

step 5

take square root both sides


x-1.5=\pm(1)/(√(2))

Convert 1.5 in a fraction number


x-(3)/(2)=\pm(1)/(√(2))


x=(3)/(2)\pm(√(2))/(2)}

User Shari
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.